2022
DOI: 10.1002/smll.202106097
|View full text |Cite|
|
Sign up to set email alerts
|

PillarX: A Microfluidic Device to Profile Circulating Tumor Cell Clusters Based on Geometry, Deformability, and Epithelial State

Abstract: Circulating tumor cell (CTC) clusters are associated with increased metastatic potential and worse patient prognosis, but are rare, difficult to count, and poorly characterized biophysically. The PillarX device described here is a bimodular microfluidic device (Pillar‐device and an X‐magnetic device) to profile single CTCs and clusters from whole blood based on their size, deformability, and epithelial marker expression. Larger, less deformable clusters and large single cells are captured in the Pillar‐device … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 88 publications
0
25
0
Order By: Relevance
“…Green et al designed a dual-mode microfluidic device PillarX consisting of a series of cylindrical devices and X-devices, which can analyze a single CTC and cluster in whole blood according to the size, deformability and epithelial marker expression of a single CTC and cluster. 129 Larger, cohesive and less easily deformed clusters and larger individual cells are captured in the column device and classified according to the size of the column gap. Smaller, deformable clusters and individual cells are then captured in X-ray devices, and separated using functionalized magnetic nanoparticles according to the expression of epithelial markers.…”
Section: Micro-nano Channel Structurementioning
confidence: 99%
“…Green et al designed a dual-mode microfluidic device PillarX consisting of a series of cylindrical devices and X-devices, which can analyze a single CTC and cluster in whole blood according to the size, deformability and epithelial marker expression of a single CTC and cluster. 129 Larger, cohesive and less easily deformed clusters and larger individual cells are captured in the column device and classified according to the size of the column gap. Smaller, deformable clusters and individual cells are then captured in X-ray devices, and separated using functionalized magnetic nanoparticles according to the expression of epithelial markers.…”
Section: Micro-nano Channel Structurementioning
confidence: 99%
“…Surprisingly, they observed that some of the clusters could maintain weak intercellular adhesion. These clusters re-arranged their shape to travel through the pillars, and then clusters re-formed in the X-magnetic device [ 83 ]. This process provided direct evidence that CTC cluster cohesion can be regulated by the dynamic expression of E-cadherin, as reflected by the adaptive alteration of cluster shapes.…”
Section: Ctc Clusters and Metastasismentioning
confidence: 99%
“…The MagRC device eventually generates a spatial profile of cell distribution that can be read out by microscopy and is capable of visualizing a small shift of marker expression in rare cells, which is highly associated with bioprocesses underneath, such as metastasis . The MagRC approach is highly biocompatibleaccording to the simulation we performed previously, the shear stress under a flow rate of 5 mL/h is 0.0004 Pa within the device . This value is relatively ignorable in comparison to the shear stress generated by the FACS sorting nozzle (typically 1–30 Pa) .…”
mentioning
confidence: 95%
“…19 The MagRC approach is highly biocompatibleaccording to the simulation we performed previously, the shear stress under a flow rate of 5 mL/h is 0.0004 Pa within the device. 34 This value is relatively ignorable in comparison to the shear stress generated by the FACS sorting nozzle (typically 1−30 Pa). 34 Hence, the cells after the MagRC are highly viable and phenotypically natural.…”
mentioning
confidence: 99%
See 1 more Smart Citation